Choir versus Solo Singing: Effects on Mood, and Salivary Oxytocin and Cortisol Concentrations - Schladt, T. Moritz; Nordmann, Gregory C.; Emilius, Roman; Kudielka, Brigitte M.; de Jong, Trynke R.; Neumann, Inga D. (Frontiers in Human Neuroscience, 2017)
The quantification of salivary oxytocin (OXT) concentrations emerges as a helpful tool to assess peripheral OXT secretion at baseline and after various challenges in healthy and clinical populations. Both positive social interactions and stress are known to induce OXT secretion, but the relative influence of either of these triggers is not well delineated. Choir singing is an activity known to improve mood and to induce feelings of social closeness, and may therefore be used to investigate the effects of positive social experiences on OXT system activity. We quantified mood and salivary OXT and cortisol (CORT) concentrations before, during and after both choir and solo singing performed in a randomized order in the same participants (repeated measures). Happiness was increased, and worry and sadness as well as salivary CORT concentrations were reduced, after both choir and solo singing. Surprisingly, salivary OXT concentrations were significantly reduced after choir singing but did not change in response to solo singing. Salivary OXT concentrations showed high intra-individual stability, whereas salivary CORT concentrations fluctuated between days within participants. The present data indicate that the social experience of choir singing does not induce salivary OXT secretion. Rather, the reduction of stress/arousal experienced during choir singing may lead to an inhibition of peripheral OXT secretion. These data are important for the interpretation of future reports on salivary OXT concentrations, and emphasize the need to strictly control for stress/arousal when designing similar experiments.